The Experimental Art - Robert Root (Journal of the Assembly for Expanded Perspectives on Learning, 2003)
Nonfiction is an experimental art, as contemporary examples make clear, and writing teachers need to show students both how meaning arises from writers' experiments with material and also how form from writers' experiments at representing meaning.